Revisiting Social Stigma and Its Consequences for Children with Intellectual Disabilities - Difa Syahidah Aulia; Amelia Rahmawati Aulia; Meisya Desma Dwi Putri; Geraldus Yoissiky; Citra Ashri Maulidina; Mohammad Arif Taboer (Universitas Negeri Surabaya, 2025)
This literature review aims to examine the various forms of social stigma faced by children with intellectual disabilities, both within the country and internationally. The method used is a literature study, which involves collecting and analyzing data from various relevant scientific research studies and synthesizing them to identify key themes that form the basis of the conclusions. The findings of this literature review indicate that social stigma toward individuals with intellectual disabilities remains a serious global challenge. Such stigma directly affects self-confidence, social participation, access to education, and the overall quality of life of the individuals concerned, as well as their families. The conclusion that can be drawn is that societal stigma has a direct impact on the self-esteem, social involvement, educational opportunities, and quality of life of individuals with intellectual disabilities and their families. A lack of public understanding is the root cause of stigma, which is further reinforced by the media, educational systems, and non-inclusive social norms.